Frontiers in Optics + Laser Science 2022 (FIO, LS) 2022
DOI: 10.1364/fio.2022.fw7e.3
|View full text |Cite
|
Sign up to set email alerts
|

Octave-Spanning Supercontinuum Generation in a Thin Si3N4 Waveguide Coated with Highly Nonlinear TeO2

Abstract: We report on octave-spanning supercontinuum generation in a 400-nm-thick silicon nitride waveguide coated with tellurite glass. An octave-spanning supercontinuum is achieved at a low peak power of 482 W using a 100-fs laser centered at 1565 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The experimental SC spectra with different levels of pump power are shown in Figure 8a and are in agreement with the simulated results in the corresponding pump power shown in Figure 8b. Hamidu [35] et al reported SC generation from a highly nonlinear tellurium dioxide (TeO 2 ) overlapping on a silicon nitride (Si 3 N 4 ) ridge waveguide with a thickness of 400 nm and a width of 1600 nm. The Si 3 N 4 chip was fabricated at the Lionix foundry using standard Si 3 N 4 LPCVD (Low-Pressure Chemical Vapor Deposition).…”
Section: Teo2mentioning
confidence: 99%
“…The experimental SC spectra with different levels of pump power are shown in Figure 8a and are in agreement with the simulated results in the corresponding pump power shown in Figure 8b. Hamidu [35] et al reported SC generation from a highly nonlinear tellurium dioxide (TeO 2 ) overlapping on a silicon nitride (Si 3 N 4 ) ridge waveguide with a thickness of 400 nm and a width of 1600 nm. The Si 3 N 4 chip was fabricated at the Lionix foundry using standard Si 3 N 4 LPCVD (Low-Pressure Chemical Vapor Deposition).…”
Section: Teo2mentioning
confidence: 99%